Self-Reported Internet Skills, Previous Knowledge and Working Memory in Text Comprehension in E-Learning - Burin, Debora Ines (2018)
We examined the contribution of Internet operational and navigation skills, previous knowledge, and working memory capacity to expository text comprehension as a lesson within an e-learning course. As different from previous studies in controlled settings; this study addressed students’ typical behavior in more ecological conditions. The first study tested self-reported Internet Skills Scale structure, reliability and concurrent validity, in a sample of 254 college students from a large Latin American public university. The second study addressed the contribution of self-reported Internet skills, previous domain knowledge, and working memory capacity to text comprehension in e-learning. Students (n = 125) read high or low previous knowledge expository science texts and answered questions about them, in an e-learning course specifically designed for research purposes, accessed remotely. They also completed working memory tests. Working memory and navigation were significantly associated with text comprehension: higher working memory, and lower scores in self-reported navigation behavior, led to better comprehension. These results have implications for instructional design and reading strategies interventions.